2021
DOI: 10.1080/09500693.2021.1900623
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresented minority students receive lower grades and have higher rates of attrition across STEM disciplines: A sign of inequity?

Abstract: Underrepresented minority (URM) students are subjected to historically rooted inequities when pursuing an education, especially in STEM disciplines with little diversity. In order to make STEM education equitable and inclusive, evidence for how students from different racial/ethnic demographics are faring is necessary. We use 10 years of institutional data at a large public US-based university to investigate trends in the majors that Asian, URM, and White students declare, drop, and complete. We find that URM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 61 publications
2
36
0
3
Order By: Relevance
“…A popular practice in STEM equity research is to observe the achievement gaps existing between majority and marginalized and minoritized students (Gouvea, 2021). A wealth of research explores how students who belong to underserved racial, gender, ability, and socioeconomic groups underperform academically in comparison to their privileged counterparts (e.g., Bastedo and Jaquette, 2011;Matz et al, 2017;Whitcomb and Singh, 2021). Focusing solely on gaps is harmful, because it centers students' identities as the reasons behind their academic failures.…”
Section: What Analytical and Interpretive Choices Can Be Made To Focus On Excellence?mentioning
confidence: 99%
“…A popular practice in STEM equity research is to observe the achievement gaps existing between majority and marginalized and minoritized students (Gouvea, 2021). A wealth of research explores how students who belong to underserved racial, gender, ability, and socioeconomic groups underperform academically in comparison to their privileged counterparts (e.g., Bastedo and Jaquette, 2011;Matz et al, 2017;Whitcomb and Singh, 2021). Focusing solely on gaps is harmful, because it centers students' identities as the reasons behind their academic failures.…”
Section: What Analytical and Interpretive Choices Can Be Made To Focus On Excellence?mentioning
confidence: 99%
“…degree is to complete the prerequisite introductory STEM courses. Unfortunately, numerous studies document significant achievement gaps in introductory course success, and subsequent attrition rates, for women and minoritized students in mathematical, physical, and biological sciences degree programs ( 9 – 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously we investigated inequities in learning for ethnic and racial minority (ERM) students in STEM disciplines using 10 years of institutional data (Whitcomb et al, 2021). We found that ERM students drop most STEM majors at higher rates compared to other students.…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%